Evaluation of Mannosidase and Trypsin Enzymes Effects on Biofilm Production of Pseudomonas aeruginosa Isolated from Burn Wound Infections - Banar, Maryam; Emaneini, Mohammad; Satarzadeh, Mhboubeh; Abdellahi, Nafiseh; Beigverdi, Reza; Leeuwen, Willem B. van; Jabalameli, Fereshteh (PloS one, 2016)
Biofilm is an important virulence factor in Pseudomonas aeruginosa and has a substantial role in antibiotic resistance and chronic burn wound infections. New therapeutic agents against P. aeruginosa, degrading biofilms in burn wounds and improving the efficacy of current antimicrobial agents, are required. In this study, the effects of α-mannosidase, β-mannosidase and trypsin enzymes on the degradation of P. aeruginosa biofilms and on the reduction of ceftazidime minimum biofilm eliminating concentrations (MBEC) were evaluated. All tested enzymes, destroyed the biofilms and reduced the ceftazidime MBECs. However, only trypsin had no cytotoxic effect on A-431 human epidermoid carcinoma cell lines. In conclusion, since trypsin had better features than mannosidase enzymes, it can be a promising agent in combatting P. aeruginosa burn wound infections.